Navigating Multiple Crises, Staying the Course on Long-term Development : The World Bank Group’s Response to the Crises Affecting Developing Countries - World Bank (Washington, DC, 2022)
The world is facing a perfect storm that has the potential to undo decades of development gains. Two years into a major worldwide pandemic, the global impact of the war in Ukraine is hitting countries that were already stressed. Fiscal space has been eroded in many developing countries by rising borrowing costs, and a decade of rising debt capped by a further surge, severely exacerbated by the pandemic. Rising inflation and weakening economic recovery are contributing to growing macroeconomic imbalances, exacerbating already high risks of debt distress and leaving many households vulnerable. In April 2022, the World Bank Group (WBG) outlined a “Roadmap” to indicate how it would support clients as they respond to the impacts of these ongoing, multiple, overlapping, and compounding crises. This follow-up paper details the WBG’s crisis response and proposes a framework tailored to the current situation. This paper is organized as follows. Section II describes the multiple crises facing countries today. Section III proposes a framework for the WBG response to the global crisis. Section IV and V describe key considerations for the operational approach to the crisis response and detail the financing envelope. Section VI underscores the need for global coordination to maximize the impact of this crisis response. Section VII concludes with key issues.